Papel da via de sinalização S100B/RAGE na apoptose e gliose reativa induzida pelas toxinas A e B do Clostridioides difficile em células gliais entéricas - Costa, Deiziane Viana da Silva (2019)
Clostridioides difficile (C. difficile) infection (CDI) continues to be the most common cause of antibiotic-associated diarrhea. EGCs is involved in intestinal motility, inflammation, and barrier function. We investigated the alterations in enteric glial cell-derived S100B expression in intestinal tissues from patients with CDI, as well as, in the mouse models, and the role of S100B signaling in TcdA and TcdB-induced S100B and IL-6 expression and apoptosis in EGCs. Expression of S100B was examined by immunohistochemistry in colonic biopsies from patients with active CDI, cecal tissues of VPI10463-infected mice and mouse ileal loop treated with TcdA. Rat EGC line CRL2690 (ATCC) was incubated with TcdA and TcdB to evaluate cell viability through MTT assay, cell morphology and apoptosis by a live-cell real-time assay. Gene expression of S100B, RAGE and IL-6 was performed by qPCR. The levels of extracellular S100B were evaluated by ELISA. NFκB and STAT3 activation was evaluated by immunofluorescence. To investigate the role of S100B/RAGE signaling, EGCs were incubated with Pentamidine, FPSZM1, LY294002 and Galiellalactone 1h before toxins challenge in presence or absence of recombinant S100B protein. S100B expression was significantly increased in mouse ileal loop tissue treated with TcdA, in cecal tissues from C. difficile-infected mice, as well as, in colonic biopsies from patients with active CDI. TcdA and TcdB significantly decreased EGC viability, induced EGC rounding and apoptosis, as well as upregulated S100B and IL-6 gene expression, increased S100B release and induced NFκB and STAT-3 activation in EGCs, but did not increase RAGE expression compared with control cells. Pentamidine, a S100B inhibitor, suppressed TcdA, but not TcdB-induced S100B and IL-6 expression. FPSZM1, a RAGE antagonist, significantly decreased TcdB and TcdA-induced IL-6 and S100B gene expression in EGCs, as well as, TcdA-induced apoptosis. Whereas LY294002, a PI3K inhibitor, decreased IL-6 expression, but not S100B, induced by both toxins. Galiellalactone (10μM), a STAT-3 inhibitor, significantly reduced TcdB and TcdA-induced S100B gene expression, as well as its release, and apoptosis on EGCs. However, galiellalactone was unable to prevent apoptosis induced by TcdA and TcdB on EGCs in presence of S100B protein (0.5 and 5μM). In addition, S100B (0.5 and 5μM) induced apoptosis on EGCs by itself. Our findings suggest that S100B/RAGE/PI3K/NFkB signaling is involved in TcdA and TcdBinduced IL-6. In addition, S100B/RAGE/STAT-3 pathway is involved in TcdB-induced S100B and IL-6 expression and TcdA-induced S100B expression and apoptosis. Whereas apoptosis induced by TcdB appears to be mediated by S100B/STAT-3 in a RAGE-independent manner.